Pengaruh Pandemi Covid-19 Terhadap Volume Penjualan PT. Surabaya Makmur Jaya Tahun 2020 - Mutmainnah; Amin Sadiqin (CV ODIS, 2021)
The impact of Covid 19 has a significant impact on various aspects of the world, including Indonesia, especially the industrial sector. This can be seen from the lethargy of the industry that many of us encounter in the form of stalled activities of some industrial sectors. Affected industries led to workforce cuts and a decrease in sales volume. This study aims to describe the volume of sales at PT Surabaya Makmur Jaya during the Covid 19 pandemic. The method used in this study is qualitative, the approach used in the form of case studies. The data source in this study is the primary data source obtained from internal data of PT Surabaya Makmur Jaya company